Laparoscopic early pregnancy diagnosis in the laboratory rat. (June 2018) - Ypsilantis, Petros; Somalou, Paraskevi; Panidou, Eleni; Simopoulos, Constantinos
Timely and accurate diagnosis of pregnancy in the laboratory rat is an invaluable endpoint in embryological and reproductive toxicology studies. The purpose of the present study was to assess the feasibility, sensitivity, accuracy and safety of laparoscopic examination of the uterus for detecting pregnancy at an early stage, and defining the number of fetuses in surviving rat models. Female Wistar rats were subjected to a two-port laparoscopic examination of their uterus from day 6 to day 10 post-coitum (pc). Mean recovery time from anesthesia was 148 ± 66 s. A postoperative 4.0 ± 1.8% body weight loss was restored in 3.9 ± 1.3 days. Uterine bulges suggestive of underlying embryonic vesicles could be detected by day 7 pc with a 0% false-negative diagnosis. Comparison of the number of laparoscopically defined uterine bulges (fetal counts) with litter size revealed a 0% underestimation rate of fetal counts, and a 42.9–87.5% overestimation rate from day 7 to day 10 pc. In conclusion, the present study introduced the laparoscopic examination of the uterus and showed it to be a feasible, reliable and safe method of early pregnancy diagnosis in the laboratory rat by day 7 pc.